The fifth cranial nerve in headaches - Edvinsson, J C A; Viganò, A; Alekseeva, A; Alieva, E; Arruda, R; De Luca, C; D'Ettore, N; Frattale, I; Kurnukhina, M; Macerola, N; Malenkova, E; Maiorova, M; et al. (The journal of headache and pain, 2020)
The fifth cranial nerve is the common denominator for many headaches and facial pain pathologies currently known. Projecting from the trigeminal ganglion, in a bipolar manner, it connects to the brainstem and supplies various parts of the head and face with sensory innervation. In this review, we describe the neuroanatomical structures and pathways implicated in the sensation of the trigeminal system. Furthermore, we present the current understanding of several primary headaches, painful neuropathies and their pharmacological treatments. We hope that this overview can elucidate the complex field of headache pathologies, and their link to the trigeminal nerve, to a broader field of young scientists.
Keywords: Migraine pathophysiology; bolesti hlavy; mozkový kmen; nervus trigeminus; Trigeminal Nerve; CGRP; obličejová bolest; Brain Stem; ganglion trigeminale; Trigeminal ganglion; Animals; lidé; Humans; Treatments; zvířata; Headache; Trigeminal Ganglion; Facial Pain; Fifth cranial nerve